Perception andcommunity development among youths in the Niger-Delta region of Nigeria - Chima, Nwaiwu James; Hamsan, Hanina Halimatusaadiah; Abu Samah, Asnarulkhadi (International Organization of Scientific Research, 2014)
This article discusses perception among youths based on the outcome results from a research conducted on Shell petroleum development company (SPDC) community development program for youths and business development in the Niger-Delta region of Nigeria. The study explores the relationship of perception to community development among youths (CDY) and the extent it can predict it. The study adopted a cross-sectional survey by using self-administered questionnaire and simple random sampling as its sampling techniques. Sample size of 322 emerged from 2125 youths who benefited from SPDC's micro credit loan designed for youths and business development in the region based on the list provided by the micro-credit scheme for agricultural development (MISCAD). Instrument of assessment in this study was derived from literatures in line with indicators of measuring each of the construct variables as the test and retest prove the instrument to be valid and reliability since the cronbach's alpha of the constructs recording not less than 0.604. Descriptive, Pearson's correlation and Standard multiple regression analyses were used to break down the data. Findings from the outcome of the result show that there is strong relationship between perception and community development (CD) among youths (r = 0.338, p = 0.0001). Furthermore, the construct of interest which shapes perception was discovered as the major predictor of CD among youth. The study recommends that increasing factor that spurs youth's interest should be encouraged in CD programs among youths.